Implementation of ESD (Education for Sustainable Development) in Climate Change Learning: A Literature Review - Susanti Indah Perwitasari; Eko Hariyono; Endang Susantini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: Education for Sustainable Development (ESD) is an educational agenda that focuses on the quality of learning outcomes and the emphasis on learning content and its contribution to future environmental sustainability, one of which is tackling climate change. Education for Sustainable Development (ESD) can be integrated into curriculum and learning. This study aims to describe and conduct a literature review of the implementation of ESD in climate change learning. Methods: This research is a literature study by screening 370 Scopus-indexed papers in the 2017-2022 time frame into 20 papers for analysis. The analysis results show that journal publications on implementing ESD in climate change learning still need to be made available despite increased research trends. The implementation that has been carried out can be through formal / school and non-formal education with learning innovations and developing curricula and policies. There is a tendency for developing learning innovations is the most widely practiced form of implementation in climate change learning. Implementing ESD in climate change learning is vital in improving the understanding, skills, and awareness of climate change. Novelty: The study reveals an urgent need to develop the right innovations, methods, and designs to implement ESD in climate change learning, especially government policies. These findings invite researchers, practitioners, governments, and communities to be involved in developing innovations, methods, designs, and policies within a sustainable framework by implementing ESD in climate change learning.